Sistem Input Output Inventaris Tools Menggunakan Long Range RFID Study Case di PLTA Sutami - Fa'iz, Muhammad; Joko Endrasmono; Sholahuddin Muhammad Irsyad; Lilik Subiyanto; Anggar Juna Puncak Pujiputra; Mustika Kurnia Mayangsari (Journal of Applied Smart Electrical Network and Systems, 2025)
The problem faced by Sutami Hydroelectric Power Plant in the management and data collection of tools is that the data collection is still done manually, and some tools are not returned to their place due to negligence in use. To support the achievement of the 5S culture (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) at Sutami Hydroelectric Power Plant, an automated tools management system is needed. In the application of the goods input and output system, many are still using low frequency RFID with a reading range of >5cm so that tapping must be done with an RFID Reader. This still has the potential for an unrecorded loan process if the item is not tapped. This research optimizes the tools management system with long range RFID. With the designed update, it is expected that the tools management system at Sutami Hydroelectric Power Plant can provide increased productivity and also achieve the 5S culture at Sutami Hydroelectric Power Plant.